An Intersectional Analysis to Explaining a Lack of Physical Activity Among Middle Class Black Women. Issue 6 (June 2014) - Ray, Rashawn
Abstract In this essay, I make the case that the intersectionality framework is useful to explain the high level of obesity among Black women. I describe how the intersectionality framework reformulates the examination of racial and gender disparities in health by deconstructing traditional frames of Whiteness and maleness. Next, I discuss key barriers that operate as mechanisms to reduce Black women's level of physical activity. Then, I provide ways to potentially combat these barriers. In doing so, I argue that being physically active is a privilege rooted in how race, place, gender, and body image converge differently on Black women's propensity to be physically active than other raced and gendered groups. Middle class Black women are excluded from class‐based privileges and experience a form of space invasion where their temporal space, geographic space, and bodily space are invaded. In this regard, this research agenda is not solely about physical activity but rather how the structural arrangements of communities contribute to healthy lifestyles.